Evaluating the microbial ecology and metabolite profile in Kazak artisanal cheeses from Xinjiang, China. (September 2018) - Zheng, Xiaoji; Liu, Fei; Li, Kaixiong; Shi, Xuewei; Ni, Yongqing; Li, Baokun; Zhuge, Bin
Abstract: Kazak artisanal cheese is one of the famous fermented food in Uighur Autonomy Region of Xinjiang, China. However, the microbial ecology in Kazak artisanal cheeses across different regions is unclear. In this study, we determined the microbial community composition through amplicon sequencing and measured the flavor profile of 10 cheese samples from different regions of Xinjiang. The associations between microbial communities, flavors and environmental factors were examined by redundancy analysis and Monte Carlo permutation test. Cheeses from different regions had different microbial communities, which was mainly reflected in the relative abundance of Lactobacillus, Streptococcus, Issatchenkia, Debaryomyces and Kluyveromyces . In addition, Pichia and Torulaspora were also the key microbial groups, according to the high relative abundance and large co-occurrence incidence in the correlation network. Using the microbe-metabolites correlation analysis, the major flavor-producing taxa were identified as Kluyveromyces, Anoxybacillus, Torulaspora, Lactobacillus, Streptococcus and Dipodascus . Environmental factors accounted for the majority of the microbial community variations, 88.54% for bacteria and 75.71% for fungi. Compared to physico-chemical factors (temperature, moisture, and pH), geographical factors (longitude, latitude and elevation) had a stronger effect on microbial communities in cheese samples from different regions of Xinjiang. Graphical abstract: Unlabelled Image Highlights: Microbiota exhibited different profiles in Kazak artisanal cheeses from different regions. The key microbial groups were observed in Kazak artisanal cheeses. The major flavor contributors were identified. Environmental factors shaped microbial and metabolic profiles. Geographical factors were more notable than physic-chemical factors shaping microbiota.